The hyaluronic acid gel promotes the formation of osteoblasts mineralized nodules and fracture callus by regulating the expression of Runx2 and osteocalcin: Hyaluronic acid gel promoting the osteoblasts mineralized nodules - Yang, Jiaquan; Liu, Yulian; Chen, Kunqiang; Liu, Muzi (Cellular and Molecular Biology, 2023)
This study aimed to investigate the effect of hyaluronic acid (HA) gel regulating the expression of Runx2 and osteocalcin (OCN) on osteoblast mineralization nodules and fracture callus formation. To achieve this aim, MC3T3-E1 cells were divided into two groups, the HA group and the control group, based on the intervention of HA gel. In addition, a fracture callus model was constructed to observe cell proliferation, cell mineralization, and fracture callus formation. Results showed that HA at different concentrations had no obvious outcome on the proliferation of MC3T3-E1 cells (P>0.05). The area of mineralized nodules in the HA intervention group (65.38±4.27) was higher than in the control (9.52±2.16, P<0.05). The expression levels of Runx2 and OCN in the HA intervention group were higher than control (P<0.05). The callus area in the HA group (110.05±4.16) and (143.16±8.84) was significantly higher as against control (72.51±6.32, 88.92±5.28) at 2 and 4 weeks after intervention (P<0.05). It was concluded that HA gel promotes the proliferation and differentiation of osteoblasts by regulation of Runx2 and OCN, and then promotes the formation of mineralized nodules of osteoblasts and fracture callus, thereby promoting fracture healing.